Penanaman Nilai-Nilai Pendidikan Agama Islam Melalui Program Ekstrakulikuler Karawitan di MA Al-Muttaqien Pancasila Sakti Klaten - Vitrotun Hasanah; Abdul Majid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the implementation of the karawitan extracurricular program at MA Al-Muttaqien Pancasila Sakti Klaten. To determine the instillation of Islamic religious education values through the karawitan extracurricular program at MA Al-Muttaqien Pancasila Sakti Klaten. To determine the results achieved in the instillation of Islamic Religious Education values through the karawitan extracurricular program at MA Al-Muttaqien Pancasila Sakti Klaten. This type of research is qualitative research, which is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. This study has two objectives, namely, the first to describe and reveal and the second to describe and explain. The type of research used in this thesis is field research, which is a type of research that seeks to collect information data regarding problems in the field. Data collection techniques with observation, interviews and documentation. The location of this research is at MA Al-Muttaqien Pancasila Sakti Klaten. The subjects of this study were the Principal of MA Al-Muttaqien Pancasila Sakti Klaten, the instructor of the karawitan extracurricular program of MA Al-Muttaqien Pancasila Sakti Klaten, the Islamic Religious Education Teacher of MA Al-Muttaqien Pancasila Sakti Klaten and the students of MA Al-Muttaqien Pancasila Sakti Klaten. The results of this study are that the karawitan extracurricular program at MA Al-Muttaqien Pancasila Sakti Klaten aims to preserve Javanese culture, especially karawitan. The implementation of the karawitan extracurricular program at MA Al-Muttaqien Pancasila Sakti Klaten is attended by students of grades X and XI which is carried out routinely once a week every Monday. Learning is carried out both in theory and practice. Supporting factors for the implementation of the karawitan extracurricular program include teachers who are competent in their fields, student interest or enthusiasm, and the existence of a karawitan extracurricular program implementation schedule. The obstacles are the facilities and infrastructure that are not yet complete. instilling the values of Islamic Religious Education through the extracurricular gamelan program at MA Al-Muttaqien Pancasila Sakti Klaten has 3 aspects, namely faith, morals and worship.